ANALISIS YURIDIS TERHADAP PELAKU TINDAK PIDANA NERKOTIKA JENIS PIL EKSTASI - Christin A. Sazqia Hutauruk; Govindo Tarigan; Rio Alvredo T.H. Sianipar; Rahmayanti Rahmayanti (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2019)
Narcotics crimes committed by the public and State officials are criminal acts and the problem of drug abuse is something that can damage the future which results in death so that it becomes an unfamiliar problem in society. And for this reason, it is necessary to have a reason and nonpenal legal policy to resolve the misuse of this ecstasy pill type, and for the public to care more about this narcotics abuse not to use or distribute narcotics. There must also be reliable or fair efforts and considerations needed for these narcotics cases. according to the law that has been stipulated, namely Law No. 35 of 2009 on narcotics from the discussion, according to the author, the abuse of narcotic pills is very fair because the considerations and articles used are very appropriate to prosecute narcotics crimes of eskills pills.